Prolonged Ileus in an Infant Presenting with Primary Congenital Hypothyroidism. (17th March 2015) - Chua, Caroline; Gurnurkar, Shilpa; Rodriguez-Prado, Yahdira; Niklas, Victoria
Abstract : Congenital hypothyroidism (CH) is the most common endocrine disorder affecting the newborn. Universal newborn screening (NBS) has virtually eliminated the static encephalopathy and devastating neurodevelopmental syndrome known as cretinism. This report describes the presentation of an infant referred by the primary pediatrician to our hospital at 12 days of age for confirmatory testing after the NBS was consistent with CH. The infant had hypoglycemia secondary to lethargy and poor feeding and required transfer to the neonatal intensive care unit for worsening abdominal distension despite normalization of serum thyroid function tests following hormone replacement. In particular, the recalcitrant ileus and secondary bowel obstruction resulted in an additional diagnostic workup and lengthened hospital day. Our report highlights the acute gastrointestinal consequences of hypothyroidism despite evidence of effective treatment. We believe that the preclinical detection and immediate therapy for CH have lessened the prevalence of this presentation in general practice, and hence practitioners are less likely to be familiar with its natural history and management.